2022
DOI: 10.1083/jcb.202205123
|View full text |Cite
|
Sign up to set email alerts
|

Quality control mechanisms that protect nuclear envelope identity and function

Abstract: The nuclear envelope (NE) is a specialization of the endoplasmic reticulum with distinct biochemistry that defines inner and outer membranes connected at a pore membrane that houses nuclear pore complexes (NPCs). Quality control mechanisms that maintain the physical integrity and biochemical identity of these membranes are critical to ensure that the NE acts as a selective barrier that also contributes to genome stability and metabolism. As the proteome of the NE is highly integrated, it is challenging to turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 143 publications
0
17
0
Order By: Relevance
“… 5 , 6 However, our understanding of analogous processes in the NE of mammalian cells has only started to emerge recently, 7 , 8 with major elements of NE turnover still remaining uncharacterized. 1 , 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 However, our understanding of analogous processes in the NE of mammalian cells has only started to emerge recently, 7 , 8 with major elements of NE turnover still remaining uncharacterized. 1 , 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…In S. cerevisiae , the Doa10 E3 ubiquitin ligase cooperates with the Asi complex in INMAD (Koch and Yu, 2019; Smoyer and Jaspersen, 2019; Mannino and Lusk, 2022). As homologs of Asi proteins are absent in S. pombe as in other species, INMAD mechanisms may be diverse among organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitination reactions involve three different classes of enzymes: E1 ubiquitin-activating enzymes, E2 ubiquitin-conjugating enzymes, and E3 ubiquitin ligases such as Hrd1 and Doa10 (human MARCHF6/TEB4). INM-associated degradation (INMAD) has been proposed as an extension of ERAD to maintain INM homeostasis, which also depends on the UPS (Foresti et al, 2014; Khmelinskii et al, 2014; Koch and Yu, 2019; Smoyer and Jaspersen, 2019; Mannino and Lusk, 2022). It has been shown that in the budding yeast Saccharomyces cerevisiae , ERAD and INMAD require additional machinery for the degradation of integral membrane proteins, involving Cdc48/p97, an ATPase associated with diverse cellular activities (AAA-ATPase), which removes the ubiquitinated proteins from the membrane before transferring them to the proteasome for degradation (Ruggiano et al, 2014; Christianson and Carvalho, 2022; Koch and Yu, 2019; Smoyer and Jaspersen, 2019; Mannino and Lusk, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that NEB-like mechanisms also contribute to the turnover of damaged INM components via a selective mode of autophagy termed nucleophagy [ 30 , 107 ] (reviewed in [ 106 ]). In yeast, autophagy can be induced when cells are starved of nitrogen or treated with the drug rapamycin.…”
Section: Neb To Sequester Inm Cargomentioning
confidence: 99%
“…In yeast, autophagy can be induced when cells are starved of nitrogen or treated with the drug rapamycin. Both treatments resulted in nuclear envelope protrusions [ 107 ] and NEB [ 30 ] followed by vacuolar removal of INM and nuclear cargo ( Figure 3c ). The autophagy receptor Atg39 is a transmembrane protein that spans the ONM [ 108 ] and connects to the luminal leaflet of the INM via membrane-binding amphipathic helices [ 30 , 107 ].…”
Section: Neb To Sequester Inm Cargomentioning
confidence: 99%